Accidental Ingestion of 35% Hydrogen Peroxide - Sean Pritchett; Daniel Green; Peter Rossos (Canadian Journal of Gastroenterology)
Hydrogen peroxide is a commonly used oxidizing agent with a variety of uses depending on its concentration. Ingestion of hydrogen peroxide is not an uncommon source of poisoning, and results in morbidity through three main mechanisms: direct caustic injury, oxygen gas formation and lipid peroxidation. A case of a 39-year-old man who inadvertently ingested 250 mL of unlabelled 35% hydrogen peroxide intended for natural health use is presented. Hydrogen peroxide has purported benefits ranging from HIV treatment to cancer treatment. Its use in the natural health industry represents an emerging source for accidental poisonings.